Sistem Pendukung Keputusan Dalam Penentuan Wisata Alam Terbaik Menerapkan Metode Operational Competitiveness Rating Analysis - Khailizah Khailizah; Budianto Bangun; Elysa Rohayani Hasibuan (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Tourism is an activity on vacation or traveling with the aim of enjoying a new atmosphere and visiting tourist attractions such as mountains, beaches, parks and others. Nature tourism is a form of tourism that involves nature as the main object or place, which takes advantage of the beauty and uniqueness of nature such as national parks, forests, mountains, beaches, lakes, rivers, and so on. In selecting nature tourism, ecological aspects must be considered to maintain environmental balance and conserve biodiversity. Social and cultural aspects must also be considered to ensure that the development of natural tourism does not harm the local community, does not damage cultural heritage and traditions and mistakes often occur in determining good nature tourism. In determining natural tourism there are various criteria, namely: Natural beauty, Cost, Atmosphere, Cleanliness and Sustainability and Facilities. From the test results obtained the best alternative with a value of 0.32125.